PENGGUNAAN KECERDASAN BUATAN DALAM KONTEKS PEMBELAJARAN DI SEKOLAH DASAR - Yohanes, Rizki Adri; Fredy; Hafsemi Rapsanjani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In the era of industrial revolution 4.0 which increasingly encourages the integration of technology in various aspects of life, primary school education has become the main focus in the application of artificial intelligence (AI) to improve the learning experience. In this context, artificial intelligence offers a potential solution to overcome challenges in the learning process at the elementary level. exploring and analyzing the use of artificial intelligence (AI) in learning in elementary schools, can make a significant contribution in preparing the young generation to face challenges in the era of the industrial revolution 4.0. This research uses a literature study method. Qualitative analysis was carried out using a systematic literature review method on various sources of research publications. Data collection was carried out by searching and documenting the latest articles published since 2023 that are relevant to this topic. A total of 13 recent articles obtained from the Google Scholar database were analyzed. The research results show that by using AI, learning can be personalized according to students' individual needs and abilities. Through intelligent tutoring systems, adaptive learning platforms, and automated assessments, AI can help teachers provide more effective and engaging learning experiences for students. Apart from that, the use of AI can also increase student engagement, reduce teacher workload, and prepare students to face the demands of the digital era. This research concludes that with the right approach, AI can be an effective tool in supporting the learning process and preparing students to face challenges in the era of the industrial revolution 4.0.